2014
DOI: 10.5935/0004-2749.20140004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of head posture on the visual acuity of children with nystagmus

Abstract: RESUMO ABSTRACTPurpose: Evaluate the relationship between the postural alignment of the head and possible interference in the view of children. Methods: We evaluated 11 children between 2 and 7 years of age of both sexes, with the visually impaired, who had nystagmus and head lock position. The test Lea Grating Acuity Test® was used to collect measurements of visual acuity. This applied on two occasions: with and without postural alignment of the head. For reliability of the postural alignment of the head, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We have previously argued that the standard clinical protocol for measuring VA does not control for aspects of visual timing, and that this may explain why studies that do not employ a psychophysical protocol tend to find somewhat larger VA changes in response to nystagmus waveform modifications (since viewing times are naturally constrained by the implicit need to move on to the next test). 6,31 In accordance with previous studies, we have demonstrated a relationship between foveation duration and VA across participants. However, within an individual, there is only a small (yet significant) relationship between the change in any aspect of nystagmus and VA, which is also consistent with previous studies that have measured VA using a staircase protocol.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have previously argued that the standard clinical protocol for measuring VA does not control for aspects of visual timing, and that this may explain why studies that do not employ a psychophysical protocol tend to find somewhat larger VA changes in response to nystagmus waveform modifications (since viewing times are naturally constrained by the implicit need to move on to the next test). 6,31 In accordance with previous studies, we have demonstrated a relationship between foveation duration and VA across participants. However, within an individual, there is only a small (yet significant) relationship between the change in any aspect of nystagmus and VA, which is also consistent with previous studies that have measured VA using a staircase protocol.…”
Section: Discussionsupporting
confidence: 92%
“…1 One might therefore presume that utilizing the null zone would cause VA to increase. Indeed, when plotted between individuals with IN, foveation duration is positively associated with VA. 5 Moreover, a study by Costa et al 6 demonstrated that the clinical VA of children with IN (as measured using the Lea Grating Acuity Test) was significantly improved by using the null zone. A recent study by Proudlock et al (IOVS 2016;57:ARVO E-Abstract 980) has found similar results, reporting that changes in gaze angle (through use of the nystagmus null zone) cause significant changes in clinically measured VA.…”
mentioning
confidence: 99%
“…Jones et al [22] and Fadardi et al [23] assessed the impact of stress and mental load on VA, respectively. Costa et al [24], Dunn et al [25] and Roberts et al [26] assessed the impact of gaze angle on VA, while two studies by Dai et al [27][28] assessed its impact on motion perception. Pascal and Abadi [29] and Tailor et al [30] each assessed the impact of visual crowding in IN.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of the wobble can depend on state of health, tiredness, stress level and direction of gaze, so that vision in nystagmus can be highly variable. Most people with nystagmus have a “null point”, which represents a head position in which the nystagmus movements are least and the vision most comfortable (Da Costa et al , 2014). Families and supporters need to allow the person to adopt their chosen null point and not try to enforce straight posture, which will worsen vision.…”
Section: Non-treatable Conditionsmentioning
confidence: 99%